The Ventilation-to-area Ratio and House Lighting Relate to the Incidence of Pulmonary Tuberculosis - Adil Jihad Muhammad; Pudji Lestari; Agung Dwi Wahyu Widodo (Althea Medical Journal, 2020)
Background: Indonesia is one of the heavy burden countries with high pulmonary tuberculosis incidence in the world. The physical condition of houses is one of the environmental factors on how the infection spreads. The objective of this study was to provide supporting facts between the physical environment of the houses and the incidence of pulmonary tuberculosis.Methods: This was an observational analytic study with a case-control design, using checklists among pulmonary tuberculosis patients (n 32) and their healthy controls (n 32). Study subjects were chosen by simple random sampling. The study was performed from March to August 2019 at the Public Health Center (Pusat Kesehatan Masyarakat, Puskesmas) in Sawahan district, Surabaya. The incidence of pulmonary tuberculosis was related to various factors, including window existence, window opening habit, ventilation-to-area ratio, humidity, temperature, lighting, and occupancy density. The collected data were analyzed using the chi-square test to assess statistical significance with a p-value <0.05 was considered significantly related.Results: The ventilation-to-area ratio (p<0.05) and house lighting (p<0.00) were related to pulmonary tuberculosis incidence, whereas other factors such as window existence, window opening habit, temperature, and occupancy density were not.Conclusions: The ventilation-to-area ratio and house lighting have been proven to be related to pulmonary tuberculosis incidence. Government regulation on building permit needs to be encouraged to reduce the spreading and the incidence of pulmonary tuberculosis.